Efficacy and safety of apixaban compared with warfarin according to age for stroke prevention in atrial fibrillation: observations from the ARISTOTLE trial - Halvorsen, Sigrun (Oxford University Press, 2014)
AIMS: The risk of stroke in patients with atrial fibrillation (AF) increases with age. In the ARISTOTLE trial, apixaban when compared with warfarin reduced the rate of stroke, death, and bleeding. We evaluated these outcomes in relation to patient age. METHODS AND RESULTS: A total of 18 201 patients with AF and a raised risk of stroke were randomized to warfarin or apixaban 5 mg b.d. with dose reduction to 2.5 mg b.d. or placebo in 831 patients with ≥2 of the following criteria: age ≥80 years, body weight ≤60 kg, or creatinine ≥133 μmol/L. We used Cox models to compare outcomes in relation to patient age during 1.8 years median follow-up. Of the trial population, 30% were <65 years, 39% were 65 to <75, and 31% were ≥75 years. The rates of stroke, all-cause death, and major bleeding were higher in the older age groups (P < 0.001 for all). Apixaban was more effective than warfarin in preventing stroke and reducing mortality across all age groups, and associated with less major bleeding, less total bleeding, and less intracranial haemorrhage regardless of age (P interaction >0.11 for all). Results were also consistent for the 13% of patients ≥80 years. No significant interaction with apixaban dose was found with respect to treatment effect on major outcomes. CONCLUSION: The benefits of apixaban vs. warfarin were consistent in patients with AF regardless of age. Owing to the higher risk at older age, the absolute benefits of apixaban were greater in the elderly.